Partisipasi Masyarakat Dalam Perencanaan Teritorial (Studi Komparasi: Borobudur dan Nantes) - Adhanani, Reny Agustine Nur (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2013)
The issue of public participation in spatial planning has become a topic of debate in many parts of the world in recent decades, as well as in Indonesia and France. Indonesia put its effort to manifest the idea of public participation through the institutionalized annual program namely Musrenbang since 2004.Â  In spite of numerous critics addressed, the program remains for nearly a decade without any significant improvement. Whilst, the presence of the organization â€œPeta Hijauâ€, despite its very limited resources, had succeeded inviting the citizens to be involved in a mapping project in the village of Borobudur. In different scale and situation, the city of Nantes with its â€œDialogue Citoyenâ€ successfully bridged the citizens and the decision makers in the process of coproduction the public policy in territorial planning since 2010. Taking a lesson learn from the practice in Borobudur and Nantes, the non technical aspect such as a strong commitment and trust building capability are ones of the key to properly bring the concept of citizen participation into reality.